The direct and indirect effects of bioactive compounds against coronavirus - Tomas M; Capanoglu E; Bahrami A; Hosseini H; Akbari-Alavijeh S; Shaddel R; Rehman A; Rezaei A; Rashidinejad A; Garavand F; Goudarzi M; Jafari SM (John Wiley and Sons Australia, Ltd and Nanchang University, Northwest University, Jiangsu University, Zhejiang University, Fujian Agriculture and Forestry University, 2022)
Emerging viruses are known to pose a threat to humans in the world. COVID-19, a newly emerging viral respiratory disease, can spread quickly from people to people via respiratory droplets, cough, sneeze, or exhale. Up to now, there are no specific therapies found for the treatment of COVID-19. In this sense, the rising demand for effective antiviral drugs is stressed. The main goal of the present study is to cover the current literature about bioactive compounds (e.g., polyphenols, glucosinolates, carotenoids, minerals, vitamins, oligosaccharides, bioactive peptides, essential oils, and probiotics) with potential efficiency against COVID-19, showing antiviral activities via the inhibition of coronavirus entry into the host cell, coronavirus enzymes, as well as the virus replication in human cells. In turn, these compounds can boost the immune system, helping fight against COVID-19. Overall, it can be concluded that bioactives and the functional foods containing these compounds can be natural alternatives for boosting the immune system and defeating coronavirus.
Keywords: COVID‐19; antiviral activity; bioactive compounds; coronavirus; functional foods; immune system